Penerapan model pembelajaran TGT (teams games tournament) untuk meningkatkan aktivitas dan prestasi belajar biologi - Made Eka Adnyana (Indonesian Journal of Educational Development, 2020)
This study aims to improve the activities and learning achievements of biology in class XI MIPA5 students of SMA Negeri 1 Kuta Selatan through the application of the TGT learning model. This research was conducted from August 7, 2019 to September 26, 2019, with the research subjects as Class XI MIPA5. The objects in this study are the activities and achievements of learning biology. Student activity data is collected through observation sheets and learning outcome data is collected through learning achievement tests arranged in the form of objective tests. The data that has been collected, then analyzed descriptively. The results of this study indicate that an increase in student activity and learning achievement after the TGT learning model is applied, this can be seen from the average student learning activities in the first cycle of 11.53 with less active criteria while in cycle II the average value of student activity is 19.83 with active criteria. The average student achievement in cycle I was 65.33 with sufficient criteria and students' learning completeness 69.44%, while in cycle II the average value of student learning achievement was 83.25 with good criteria and student learning completeness 97%. Penelitian ini bertujuan untuk meningkatkan aktivitas dan prestasi belajar biologi pada siswa kelas XI MIPA5 SMA Negeri 1 Kuta Selatan melalui penerapan model pembelajaran TGT. Penelitian ini dilaksanakan dari tanggal 7 Agustus 2019 sampai 26 september 2019, dengan subyek penelitian adalah kelas XI MIPA5. Obyek dalam penelitian ini adalah aktivitas dan prestasi belajar biologi. Data aktivitas siswa dikumpulkan melalui lembar observasi dan data hasil belajar dikumpulkan melalui tes prestasi belajar yang disusun dalam bentuk tes objektif. Data yang telah terkumpul, kemudian dianalisis secara diskriptif.Hasil penelitian ini menunjukkan bahwa terjadi peningkatan aktivitas dan prestasi belajar siswa setelah diterapkan model pembelajaran TGT, ini dapat dilihat dari rata-rata aktivitas belajar siswa pada siklus I sebesar 11,53 dengan kriteria kurang aktif sedangkan pada siklus II nilai rata-rata aktivitas siswa adalah 19,83 dengan kriteria aktif. Rata-rata prestasi belajar siswa pada siklus I adalah 65,33 dengan kriteria cukup dan ketuntasan belajar siswa 69.44%, sedangkan pada siklus II nilai rata-rata prestasi belajar siswa adalah 83,25 dengan kriteria baik dan ketuntasan belajar siswa 97%.